The impact of Pseudomonas monteilii PN1 on enhancing the alfalfa phytoextraction and responses of rhizosphere soil bacterial communities in cadmium-contaminated soil. Issue 6 (December 2021) - Wang, Yan; Yang, Ru; Hao, Jianjun; Sun, Mengqi; Wang, Hongyu; Ren, Hejun
Abstract: Cadmium (Cd) is a hazardous contaminant when dispersed into soil. It is toxic to plants and further decreases the efficiency of phytoremediation. To improve plant tolerance to Cd, applying plant-associated bacteria is an effective way. This work aimed to determine the effect of a plant growth promoting bacterium Pseudomonas monteilii strain PN1 on alfalfa ( Medicago sativa L.) growth, Cd phytoextraction, and bacterial communities in rhizosphere. A pot trail was performed with alfalfa planted in soil containing Cd at various concentrations and drenched with PN1 suspension. Plants and soil were sampled for biochemical and microbial analyses. Results showed that alfalfa growth was negatively correlated with Cd concentration. However, PN1 inoculation enhanced the growth of alfalfa, and augmented the capacity of Cd phytoextraction. Phytohormone (indole-3-acetic acid) production and antioxidant enzymatic activities (guaiacol peroxidase, superoxide dismutase, and catalase), and 1-aminocyclopropane-1-carboxylic acid deaminase activities of alfalfa were enhanced, which indicated PN1 might mitigate Cd stress. There was a negative impact of Cd on the rhizosphere bacterial communities. However, PN1 can restore the bacterial community in Cd contaminated soil to a certain level. Relative abundance of beneficial bacteria in soil increased and their interactions were strengthened in the presence of PN1 under Cd stress, which was indicated by increased alfalfa growth. All the activities on alfalfa and bacteria in soil facilitated the adaptability of plant-bacteria systems to Cd stress. Thus, the association of alfalfa with PN1 can be a potential biological system for in-situ remediating Cd-contaminated soil. Graphical Abstract: ga1 Highlights: PN1 enhanced alfalfa growth by elevating enzymatic activities and IAA production. PN1 augmented the capacity of Cd phytoextraction from soils. PN1 resulted in heavy-metal-tolerant bacteria and PGPB enriched in soils. The association of alfalfa with PN1 can be a potential candidate for in situ remediation of Cd-contaminated soil.